Distribution practice method of badminton lob punch accuracy - Hadjarati, Hartono; Haryanto, Arief Ibnu; Prasetyo, Agung; Ilham, Al (Jorpres (Jurnal Olahraga Prestasi), 2023)
The aim of this research is to determine the effect of the distribution practice method on the accuracy of lob shots in badminton. This study employs an experimental method, utilizing a One Group Pretest and Posttest design. The sample consists of 11 athletes. Data collection techniques involve tests and measurements, with the research instrument being a lob shot accuracy test. Data analysis is performed using the t-test formula at a significance level of 5%. The results of hypothesis testing indicate that there is an influence of the distribution practice method on the accuracy of badminton lob shots. Therefore, the conclusion is that there is an impact of the distribution practice method on the accuracy of lob shots in badminton. This demonstrates that the distribution practice training method is suitable for improving the accuracy of badminton lob shots